EMERGENCE OF MULTIDRUG RESISTANT BACTERIA AMONG PATIENTS WITH RESPIRATORY TRACT INFECTIONS - Omaima S Al-Qaissy,; Ahmed S. K. Al-Khafaji, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
In this study, 25 Pseudomonas aeruginosa isolates were diagnosed in 160 clinical samples collected from patients attending the Tuberculosis Institute/ Medical city and Al-Muhmodia Public Hospital, in addition to a number of private laboratories in Baghdad during the period from September 2020 to February 2021. The bacterial isolates from clinical samples were biochemically diagnosed by API® 20E system then further identified by VITEK 2 system. P. aeruginosa represented the most prevalent bacteria in lower respiratory tract specimens. These isolates showed moderate to high susceptibility towards 11 antimicrobial agents tested in this study except that of ceftazidime and ceftriaxone. Extra-chromosomal resistance of the top three of the most resistant P. aeruginosa isolates were subjected for molecular investigation. Bacterial transformation of E. coli S1 cells with plasmid DNA extracted from the selected P. aeruginosa isolates exhibited increased resistance to ceftazidime and penicillin G. The data clearly suggest that the plasmid DNA content is implicated in enhancement of P. aeruginosa resistance through horizontal transfer of extra- chromosomal beta lactam resistance associated genes.